ANALISIS KEKUATAN MEREK YAMAHA JUPITER MX MELALUI COMMUNITY DEPTH INTERVIEW - Hijrah Wahyudi (Jurnal Ekonomi Integra, 2016)
The purpose of this study was to determine the strength of the brand Yamaha Jupiter MX when viewed from the aspect of advantages and disadvantages which become the basis of the formation of a community of users. To answer the research question, used qualitative analysis techniques, which collects information from informants that members of the community Jupiter MX, then the results are summarized in a complete accurate. The determination is based on the speaker or respondent snowball sampling method, if after the interview, the initial group is asked to appoint another person to be interviewed. Then, new to the respondents, the researchers also ask another name that .fits into the target. With this technique will produce a relatively homogeneous sample, because respondents tend to appoint people who have the same characteristics with them.The study concluded that the strength of the brand Yamaha Jupiter MX is already well marked by numerous communities popping its kind in the real world or in cyberspace. Of these communities can be assembled several advantages and disadvantages Yamaha Jupiter MX which can later be used as additional information for the Yamaha factory.